HYGROSCOPIC PROPERTY OBSERVED IN Nd2 Si2 O7 COATINGS - Saeed, Muhammad; Chaudhary, Khaliq (Journal of Research (Science), 2002)
Nd2 Si2 O7 coatings have been prepared on Si (100) wafers by screen-printing method. The 80μm thick coatings were prepared from a mixture paste of high grade SiO2 and Nd2O3 powders. The samples were characterized, by X-ray diffraction, IR-Spectrometry and optical microscopy. Tetragonal Type-A structure of Nd2 Si2 O7 coatings with lattice constants a=b=6.8Å and c=24.7Å was obtained for samples sintered at 1000°C for 24 hrs. The porous Nd2 Si2 O7 coatings were found to be hygroscopic. The moisturized coatings indicated strong IR absorption in the 1600-3000 cm-1 range.